Pollen tube growth following compatible and incompatible intraspecific pollinations in Petunia hybrida. - Herrero, M; Dickinson, H (Springer-Verlag, 1980)
The observation that both compatible and incompatible pollen tubes grow at identical speeds on the stigma in many plants with 'gametophytically controlled' self-incompatibility (SI) systems has, in Petunia, been extended to cover all other facets of pollen behaviour on this tissue. On entry into the stylar transmitting tissue both types of tubes accelerate, but the compatible achieve a higher terminal velocity than do the incompatible, which eventually slow and stop. Grafting experiments show that the top 1 mm of the stylar tissue can play an important rôle in determining the future development of the pollen tube. Following mixed pollinations, proportionally too many 'compatible' pollen tubes reach the ovary than would be expected from the results of 'pure' compatible and incompatible pollinations indicating that incompatible pollen in some way helps 'prime' the style for growth of compatible pollen tubes. This data is considered in terms of recent structural studies of these tissues, and related to the pollination conditions pertaining to Petunia populations in the field.